National Bank of Poland : The Road to Indirect Instruments - Ugolini, Piero (Occasional Papers; Occasional Paper ;, 1996)
Poland was the first centrally planned economy in Eastern Europe to leave the Soviet bloc and introduce systemic reforms in all sectors of the economy. The transformation of the National Bank from a monobank to an institution of a market-based system and the Polish financial sector into a market-oriented banking system was an important element of the reform process and received strong support from the IMF and the international community. This paper describes the steps taken by the National Bank, analyzes the monetary situation, and makes recommendations.